ABC News Poll of Public Opinion on Crime, December 1982 ([Verlag nicht ermittelbar], 1984)
This special topic poll is part of a continuing series of monthly surveys that solicit public opinion on the presidency and on a range of other political and social issues. In this poll, respondents were questioned regarding their perceptions of crime and the criminal justice system. Questions assessed the respondents' fear of crime, perceptions of the seriousness of crime in the United States, evaluation of the judicial and penal systems, assessment of police performance, and confidence in the ability of the police to prevent crime. The poll also asked for respondents' opinions about President Ronald Reagan's policies, the state of the economy, and government spending. Demographic information was collected, including the respondent's sex, age, education level, race, and income level.